Why Australian History Matters - Bridge, Carl (History compass, 2003)
I have been teaching Australian history to students in the University of London on and off over the last fifteen years. Most of the class are young Britons, and there is a scattering of exchange students from other European universities, the Americas and Asia. It is a perennially popular subject and I often wonder why? One answer, better than it seems at first sight, is the mountaineer’s: ‘because it is there’. But there are certainly some things that attract students to Australian history more than others. There is a fascination with the exotic and the natural wonders. Students are particularly interested in the Aboriginal past and culture. And they are curious to explore what European and other immigrants and their descendants have achieved when they have a chance to invent a society de novo. There is also an interest in how a country of predominantly European traditions has negotiated its position permanently anchored as it is in Pacific Asia. As our London students all study Australian history along with courses on the histories of other countries and movements, there is also considerable opportunity for comparative work, and this offers perspectives that do not naturally occur to historians studying Australia from within.